Exploring the Challenges Faced by the Urban Squatter Dwellers in Sentul, Kuala Lumpur, Malaysia - Yaacob, Mahazril ‘Aini; Abdul Patah Hassan, Nurul Zulaikha (Journal of Population and Social Studies [JPSS], 2023)
Malaysia has experienced rapid urbanization, leading to congestion and a shortage of adequate housing. For those who cannot afford housing due to the high prices of houses, such as marginalized and low-income groups, squatting becomes an alternative for viable housing solutions. Many have moved into urban squatter zones in search of alternate housing. Drawing on Malaysia as a case study, this study explores the challenges urban squatter dwellers face and how it affects their well-being. This study used Participatory Action Research (PAR) and Delphi Techniques to conduct in-depth interviews with fourteen key informants in Kuala Lumpur. It analyzed the results using the thematic analysis method. Findings revealed that they faced challenges associated with social issues, housing quality, housing environment, and finances. These challenges have affected their safety, comfort, social relationships, and health. It is suggested that the government should adequately design inclusive policies and programs to resolve this predicament and enhance these dwellers’ quality of life. Since studies on urban squatters in Malaysia are scarce, this study provides insight into the country’s urban poverty problem. Furthermore, the findings can be applied to other developing countries with characteristics like Malaysia.